Genome-wide identification and characterization of microRNA genes and their targets in flax (Linum usitatissimum) - Barvkar, Vitthal T.; Pardeshi, Varsha C.; Kale, Sandip M.; Qiu, Shuqing; Rollins, Meaghen; Datla, Raju; Gupta, Vidya S.; Kadoo, Narendra Y. (Planta, 2013)
MicroRNAs (miRNAs) are small (20-24 nucleotide long) endogenous regulatory RNAs that play important roles in plant growth and development. They regulate gene expression at the post-transcriptional level by translational repression or target degradation and gene silencing. In this study, we identified 116 conserved miRNAs belonging to 23 families from the flax (Linum usitatissimum L.) genome using a computational approach. The precursor miRNAs varied in length; while most of the mature miRNAs were 21 nucleotide long, intergenic and showed conserved signatures of RNA polymerase II transcripts in their upstream regions. Promoter region analysis of the flax miRNA genes indicated prevalence of MYB transcription factor binding sites. Four miRNA gene clusters containing members of three phylogenetic groups were identified. Further, 142 target genes were predicted for these miRNAs and most of these represent transcriptional regulators. The miRNA encoding genes were expressed in diverse tissues as determined by digital expression analysis as well as real-time PCR. The expression of fourteen miRNAs and nine target genes was independently validated using the quantitative reverse transcription PCR (qRT-PCR). This study suggests that a large number of conserved plant miRNAs are also found in flax and these may play important roles in growth and development of flax.
Keywords: Digital expression analysis; Gene cluster; Linseed; miRNA; MiRNA target transcript; Promoter analysis